Colorism in employment: Hearing the voices of “Waiguoren” teachers in China - Castulo, Nilo (Journal of International Students, 2026)
Despite the growing body of literature on international students and foreign teachers in China, research on the transition of international students from the Global South into English-teaching roles remains limited. This study fills this gap by exploring international students’ experiences of their transition from being international students to being foreign teachers. Five international graduates working as foreign English teachers in China were interviewed using a qualitative case study approach. The key findings of the study revealed that international students’ key motivations for remaining in China are driven by economic opportunity, cultural exposure, and community inclusion, while systemic challenges, such as job instability, language barriers, excessive workload, and wage disparities rooted in colorism, are also highlighted. The originality of this study lies in its focus on marginalized foreign teachers labeled waiguoren, whose experiences are often shaped by racialized labor segmentation and neoliberal educational market exploitation.